2019
DOI: 10.22336/rjo.2019.54
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of flow velocity in ophthalmic artery between glaucomatous and normal subjects

Abstract: Purpose: To study the hemodynamic parameters in ophthalmic artery (OA) using color Doppler imaging in subjects with primary open-angle glaucoma (POAG), normal-tension glaucoma (NTG) and age matched normals. Methods: Sixty-eight eyes of 68 subjects (41 males and 27 females) constituted material for this prospective observational study. They were divided into three groups; Group A had 24 patients with POAG, Group B had 18 patients with NTG and Group C had 26 normal subjects. They underwent CDI of OA. The outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…POAG increases the resistance in ocular hemodynamics and damages its structure. Increased arterial RI with POAG was also reported previously 1,24 . Considering the data in Table 2, both OA and CRA seem to be suitable vessels to investigate vascular aspects of glaucomatous optic neuropathy as the RI values estimated in each responded well in the POAG patients.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…POAG increases the resistance in ocular hemodynamics and damages its structure. Increased arterial RI with POAG was also reported previously 1,24 . Considering the data in Table 2, both OA and CRA seem to be suitable vessels to investigate vascular aspects of glaucomatous optic neuropathy as the RI values estimated in each responded well in the POAG patients.…”
Section: Discussionsupporting
confidence: 76%
“…Increased arterial RI with POAG was also reported previously. 1,24 Considering the data in Table 2, both OA and CRA seem to be suitable vessels to investigate vascular aspects of glaucomatous optic neuropathy as the RI values estimated in each responded well in the POAG patients. Thus, co-evaluation of GCC, RNFL, and RI-OA and RI-CRA parameters may be a better approach to detect the progression of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…With this study, we showed that OA-RI and CRA-RI values were significantly higher in XFG group (11,12,23) . Tiwari et al (24) found high RI values in both primary open-angle and normotensive glaucoma. Risk factors independent of IOP, such as impaired ocular/ retrobulbar perfusion, which are more prominent in XFG, may further increase glaucomatous damage rate seen in XFG (25) .…”
Section: Discussionmentioning
confidence: 96%
“…found the RI and PI values of 0.93 ± 0.12 and 2.8 ± 0.42, 0.84 ± 0.02 and 1.32 ± 0.20, and 0.77 ± 0.03 and 1.80 ± 0.17, respectively, in cases of POAG, NTG, and normal controls, which reemphasizes the fact that decreased blood flow may play a role in the pathogenesis of POAG. [ 17 ] A separate group for NTG was not accorded in our study as IOP was not used as a determinant factor for the diagnosis of POAG.…”
Section: Discussionmentioning
confidence: 99%